Energy-Efficient Full-Duplex MAC Protocol Design for Air–Terrestrial Communication - Kim, Tae Yoon; Kim, Jin Ki; Lee, Won Jae; Jung, Soyi; Kim, Jae Hyun (Journal of Communications and Networks, 2023)
Wireless communication using unmanned aerial vehicles (UAVs), such as drones, is expected to be a promising solution for improving spectral efficiency in 5G wireless networks. Moreover, full-duplex (FD) has been in the spotlight as a key technology for improving network performance. In this work, we design an energy-efficient medium access control (MAC) protocol for a UAV base-station (UAV–BS) aided FD wireless communication network and demonstrate a comprehensive analytical model considering the FD pair probability. In the proposed FD MAC protocol, the FD UAV-BS focuses on energy efficiency when establishing the FD pair. Throughput is also enhanced by transmitting downlink data without decreasing the uplink data rate. We consider the FD pair probability to improve the accuracy of the analytical model. Although the FD pair probability is an important parameter for performance analysis, it has rarely been addressed in most previous works. We analyze FD pair probability according to the altitude of the FD UAV-BS and the node transmission power. The analytical model can reflect an actual network better than prior works by considering the FD pair probability. Through extensive simulations using MATLAB and the Riverbed Modeler, we verified the superiority of the proposed FD MAC protocol and the accuracy of the analytical model.
Keywords: Aerial vehicle; Energy efficient; Full-duplex; Full-duplex pair probability; Medium access control protocols; Protocol design; Terrestrial communication; Unmanned aerial vehicle base station; Wireless communications; Full-duplex; full-duplex pair probability; MAC protocol; unmanned aerial vehicle base station